Creating community: The blog as a networking device - Wiebrands, Constance (2006)
The so-called Information Age is having an interesting and often challenging impact on librarianship as a profession. Librarians are constantly called on to embrace change, to evolve and to adopt new technologies and practices, to better meet the needs of our varied clientele. The author argues that a strong sense of professional identity and community is vital for librarians if we are to meet these challenges. The blog, one of the new 'conversational technologies' that has arisen in recent years, has a part to play in creating and supporting our professional communities. This paper considers the place of blogs in librarians' professional practice. It defines blogging and the blogosphere, and examines them in the context of Bechtel's call for libraries to be 'centres of conversation'. Despite having been criticised for being over-indulgent, frivolous or a waste of time, the blog can be used as a tool to build trust, share knowledge, and raise and discuss professional issues within librarianship. The author informally surveyed thirty six librarian bloggers from around the world, asking them to consider how blogs fit into their professional practice. The issue of library blogs is also examined.